The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/17549500802495581
|View full text |Cite
|
Sign up to set email alerts
|

Verbal working memory in Specific Language Impairment: The effect of providing visual support

Abstract: Children with Specific Language Impairment (SLI) are known to exhibit difficulties on auditory working memory (WM) tasks. This study investigated the impact of providing visual support on children's performance on an auditory WM task. Three groups of 18 children participated. The groups were children with SLI, age matched, and language matched control children. Participants completed 4 digit recall tasks using different combinations of auditory and visual input and output for a digits forwards (DF) recall cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Backward digit span tasks require children to repeat lists of digits that vary in length in reverse order. Results show that children with SLI, aged 4 to 12 years, have lower backward digit span scores than age-matched controls (Briscoe & Rankin, 2009; Frizelle & Fletcher, 2015; Lum et al, 2012; Vugs et al, 2014; for studies that found trends but not significant differences, see Petruccelli, Bavin, & Bretherton, 2012; Quail, Williams, & Leitão, 2009). Counting span tasks ask children to count the number of objects in successive arrays, and then recall the number of objects in each array at the end of the sequence.…”
Section: Working Memory Deficits In Children With Slimentioning
confidence: 97%
“…Backward digit span tasks require children to repeat lists of digits that vary in length in reverse order. Results show that children with SLI, aged 4 to 12 years, have lower backward digit span scores than age-matched controls (Briscoe & Rankin, 2009; Frizelle & Fletcher, 2015; Lum et al, 2012; Vugs et al, 2014; for studies that found trends but not significant differences, see Petruccelli, Bavin, & Bretherton, 2012; Quail, Williams, & Leitão, 2009). Counting span tasks ask children to count the number of objects in successive arrays, and then recall the number of objects in each array at the end of the sequence.…”
Section: Working Memory Deficits In Children With Slimentioning
confidence: 97%
“…Adding visual cues to the auditory signal may reduce the working memory load for the processing of audiovisual speech signals for the aforementioned reasons, and there are data to support this (Mousavi et al, 1995; Quail et al, 2009; Brault et al, 2010; Frtusova et al, 2013). Neuroimaging studies have shown that the superior temporal sulcus plays a critical role in audiovisual speech perception in both optimum and degraded listening conditions (Nath and Beauchamp, 2011; Schepers et al, 2013).…”
Section: Cognitive Demands Of Audiovisual Speech Perceptionmentioning
confidence: 99%
“…Moreover, teaching through the art of loving must question why they are teaching, how they are teaching, and then what they are teaching which are known naturally. The lecturers should realize that cognitive development does not happen in the absence of attendant physical, moral, emotional, and spiritual development [20].…”
Section: Lovingmentioning
confidence: 99%